The relationship of physical exercise with the level of academic marks among university students - Luh Ita Mahendrayani; Anak Agung Putra Laksana (Physical Therapy Journal of Indonesia, 2023)
Background: Sports activities are an educational process that utilizes physical exercise to produce changes in the quality of individuals in terms of physical, mental, and emotional. In addition, poor physical health can be an internal factor that can interfere with concentration during lectures. This study aimed to determine whether there was a relationship between physical exercise and the academic level of university students. Methods: The population in this study were all second-semester sports students and were selected using cluster random sampling technique. In this study, the sample used was 78 second-semester sports students. Data collection using IPAQ (international physical activity questionnaire) questionnaire and GPA (grade point average). After the data was collected, the data was analyzed using the Chi-Square Correlation test. Results: After the results of the data analysis, a significance value of 0.700> 0.05 was obtained. Conclusion: Physical exercise has no significant relationship with students' academic grades.